Penetration depth of irrigants into root dentine after sonic, ultrasonic and photoacoustic activation. (27th March 2019) - Galler, K. M.; Grubmüller, V.; Schlichting, R.; Widbiller, M.; Eidt, A.; Schuller, C.; Wölflick, M.; Hiller, K.‐A.; Buchalla, W.
Abstract: Aim: To compare penetration depths of endodontic irrigants into the dentinal tubules of extracted teeth when using several activation methods. Methodology: The root canals of 90 extracted human teeth were prepared to size 40, .06 taper. The straight and round‐shaped root canals were distributed randomly into six groups, and final irrigation was performed with EDTA and sodium hypochlorite as follows: (I) manual dynamic activation, (II) Ultrasonic, (III) Sonic, (IV) PIPS (photon‐induced photoacoustic streaming, (V) SWEEPS (shock‐wave enhanced emission photoacoustic streaming) and (0) control without final irrigation or activation. Subsequently, methylene blue was inserted into the canals and activated according to the groups (I–V). Teeth were sectioned horizontally, imaged under a light microscope, and dye penetration depths were measured in six sections per tooth and 24 points on a virtual clock‐face per section. Data were analysed statistically by nonparametric tests for whole teeth and separately for coronal, middle and apical thirds. Results: Penetration of dye into the dentinal tubules was lowest for the controls. Median penetration depths amounted to 700–900 μm for groups I–V with differences in the apical thirds between group I and the other test groups. Minimum penetration depths were significantly greater for PIPS in the apical thirds ( P ≤ 0.046). Conclusions: Greater penetration depths occurred in the apical thirds for ultrasonic, sonic and laser‐induced activation compared to manual dynamic activation. PIPS was associated with deeper penetration of irrigants. The novel SWEEPS mode did not increase irrigant penetration.